Optimasi Tablet Hisap Ekstrak Etanol Daun Sembung (Blumea balsamifera (L.) Dc) Dengan Kombinasi Pengisi Laktosa Dan Manitol Terhadap Sifat Fisik Tablet - Mangkusari, Tri; , Erindyah R. Wikantyasning, Ph.D., Apt (2017)
Ethanolic extract of sembung leaves (Blumea balsamifera (L.) DC) contains saponin which has antimicrobial activities. Sembung leaves extract was formulated into lozenges to make it practical and acceptable. This study was aimed to determine the effect of variation in the ratio of mannitol-lactose as a binder to the granule's quality and physical properties of lozenges and to obtain the optimum formulas. The ratio of mannitol and lactose concentration applied is FI (100:0), FII (75:25), FIII (50:50), FIV (25:75) and FV (0:100). Design Expert 10.0.3.1 (trial) with Simplex Lattice Design method applied to determine the optimum formula of the lozenges based on granule quality parameters and physical properties of tablet such as angle of repose, compressibility, granule's flow rate, tapped density, friability, weight uniformity, hardness, dissolve time and flavor acceptance. Statistical test of One-Sample T-Test used statistically to analyze the proximity between verification result and predicted result. The results showed that 16% mannitol and 84% lactose is the optimum formulas. Binder dominated by larger proportion of lactose than mannitol increases granule's flow rate, hardness, soluble time, flavor acceptance and decreases angle of repose, tapped density, compressibility, friability, weight uniformity of lozenges. Statistical result of One-Sample T-Test shows there's no significant differences between verification result and predicted result. The data is valid because all parameters has p value > 0,05.